CH4 and DIC concentration - spatial from Feresjön, 2020-07-13–2022-10-19 - Asa Research Station (Swedish University of Agricultural Sciences, 2026)
As part of the SITES Water GHG chamber program, surface water samples for methane (CH4) and dissolved inorganic carbon (DIC) analysis were collected at various locations in the lake. Data contains the CH4 and DIC concentration.
Asa Research Station (2026). CH4 and DIC concentration - spatial from Feresjön, 2020-07-13–2022-10-19 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/hmuwgN3D-dRxjpfnFI1pilVg
Keywords: SITES; Inorganic carbon; Methane concentration; Time instant; Time instant; Latitude; Latitude; Longitude; Longitude; Water depth; Water depth; Water temperature; Water temperature; Dissolved methane; Dissolved methane; Dissolved inorganic carbon; Dissolved inorganic carbon; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap